Prevalensi Global Skizofrenia dan Gangguan Psikotik Lainnya di Kalangan Tunawisma dan Implikasinya - Wasiaty, Wasiaty; Nihayati, Hanik Endang; Tristiana, Rr. Dian (Journal of Telenursing (JOTING), 2024)
This systematic review aims to determine the global prevalence of schizophrenia and other psychotic disorders among homeless people and its implications. The method we used was to search for articles that determined the prevalence of schizophrenia and other psychotic disorders among homeless people in Scopus, Web of Science, Science Direct, PubMed, and Google Scholar that were published in English between 2018-2022. Eligibility of study articles was assessed using the Joanna Briggs Institute guidelines. The results of this systematic review were 114 articles from five databases: 46 articles in Scopus, 28 articles in PubMed, 20 articles in Science Direct, 10 articles from PsycoINFO, and 10 articles from Google Scholar. The results of the selection of articles that met the inclusion criteria were 10 articles, then given serial numbers and analysis of the articles was carried out to facilitate the review process. Selected articles will be presented in PRISMA format. The prevalence of schizophrenia was 13.20% for studies conducted in or after 2010, and 8.88% for studies conducted before 2010, while the prevalence of psychosis was 24.44%. In conclusion, the prevalence of schizophrenia and other psychotic disorders among homeless people is still very high. This is not only a nursing problem, but also a multidimensional social, economic and social problem that requires hard work from us (nurses) to handle it. Key words: Homeless, Mental Disorders, Psychotic, Schizophrenia